Neural responses to threat and reward and changes in inflammation following a mindfulness intervention. (March 2021) - Dutcher, Janine M.; Boyle, Chloe C.; Eisenberger, Naomi I.; Cole, Steve W.; Bower, Julienne E.
Abstract: Objective: Mindfulness meditation has been shown to reduce distress and increase well-being among individuals with chronic disease, including breast cancer survivors. However, the neural correlates of these changes and their links with inflammatory biology are not yet known. The present study examined whether a mindfulness meditation intervention was associated with changes in neural responses to threat and reward from pre- to post-intervention, and whether those neural changes were associated with changes in markers of inflammation in breast cancer survivors. Methods: This was a single-arm trial of a standardized, validated 6-week mindfulness meditation intervention. Participants were 20 women who had been diagnosed and treated for early-stage breast cancer. Participants provided peripheral blood samples and underwent a 90-minute neuroimaging scan before and after the intervention, with a focus on tasks known to elicit activity in threat- and reward-related neural regions. Results: There were significant changes in neural responses to the two tasks of interest from pre to post-intervention ( p s < 0.042). Participants showed significant reductions in amygdala activity in response to threatening images and significant increases in ventral striatum activity to rewarding images from pre- to post-intervention. Although changes in amygdala activity were not correlated with inflammatory markers, increases in ventral striatum activity were correlated with decreases in circulating concentrations of the proinflammatory cytokine IL-6 and the inflammatory marker CRP. Conclusions: These results, while preliminary, suggest that while a mindfulness meditation intervention can alter neural responses to both threat and nonsocial reward-related stimuli, changes in neural reward activity may be more closely linked to changes in circulating levels of inflammation. Highlights: Decreased amygdala activity to threatening images after a mindfulness meditation intervention with breast cancer survivors. Increased VS activity to nonsocial reward images after a mindfulness meditation intervention with breast cancer survivors. Increases in VS activity to nonsocial reward were associated with decreases in circulating levels of IL-6 and CRP. Explores mindfulness-related changes in neural responses to threat and reward and links to change in inflammation.